PENGARUH PENGGUNAAN MEDIA DIORAMA TERHADAP HASIL BELAJAR IPAS SISWA KELAS III SD - Zulfikar Yaqin; Mohammad Baihaqi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Learning media encompasses all devices or resources that can be utilized to support the teaching and learning process for students. The presence of learning media provides significant benefits for teachers in delivering subject matter and can improve student learning outcomes. Learning is a relatively permanent change in behavior resulting from past experiences or from purposeful or planned learning. A diorama is a three-dimensional depiction of a scene or scene replicated at a smaller scale with the intention of illustrating a specific event or situation. This study used a quantitative approach with a correlational survey method. This quantitative approach was chosen because the study aimed to determine the effect of using dioramas on third-grade students’ science learning outcomes through statistical analysis. The results of this study indicate that the use of dioramas did not significantly affect third-grade students’ science learning outcomes. This finding suggests that student learning outcomes are influenced not only by learning media but also by various other factors, such as students’ initial abilities, learning motivation, the learning environment, teacher competence, and the learning strategies implemented.